Metabolomics Unveiled: Decoding Platelet Dynamics in Smokers, and Head-Neck Cancer Patients - Tanios, Anthony Nasr (AUC Knowledge Fountain, 2023)
This study aimed to investigate the metabolomics profiles of platelets in smokers and head and neck cancer patients compared to normal healthy donors. This study analyzed the metabolomics profile of the platelets from smokers and cancer patients compared to healthy individuals. Samples were collected and processed by the research group of Prof. Dr. Barbara Wollenberg at the Klinikum Rechts der Isar-Technical University of Munich. The data analysis was performed at the Technical University in Munich (TUM). Untargeted metabolomics profiling was conducted using both hydrophilic interaction liquid chromatography (HILIC) and reverse-phase (RP) chromatography in both positive and negative ionization modes. This comprehensive approach allowed for the analysis of a wide range of metabolites. Additionally, targeted metabolomics analysis was performed, focusing on 71 specific metabolites. This targeted analysis encompassed nucleotides, amino acids, and 18 different acylcarnitine, including key metabolites such as taurine and betaine. These metabolites were selected based on their relevance and involvement in various metabolic pathways. The results revealed significant alterations in nucleotide, amino acid, and acylcarnitine metabolism. These findings were confirmed using targeted methods, and it was observed that these metabolites were upregulated in both smokers and cancer patients. The platelets of smokers exhibited higher susceptibility to activation due to increased concentrations of ADP and ATP. Targeted profiling also indicated that the metabolomics profile of smokers was closer to that of cancer patients. Furthermore, increased levels of acylcarnitine’s were consistently observed in both plasma samples and platelets of smokers compared to non-smoking healthy donors. This finding suggests mitochondrial dysfunction in fatty acid metabolism. Overall, this study provides valuable insights into the metabolomics profiling of platelets in smokers and cancer patients. The results highlight significant alterations in nucleotide, amino acid, and acylcarnitine metabolism, indicating potential disruptions in cellular energy production and mitochondrial function. The study emphasizes the impact of smoking on platelet metabolism and suggests that smoking may induce metabolic changes resembling those observed in cancer patients. These findings contribute to our understanding of the metabolic consequences of smoking and may have implications for the development of targeted interventions to mitigate associated health risks.